Recombinant Sendai virus vectors for activated T lymphocytes - Okano, S; Yonemitsu, Y; Nagata, S; Sata, S; Onimaru, M; Nakagawa, K; Tomita, Y; Kishihara, K; Hashimoto, S; Nakashima, Y; Sugimachi, K; Hasegawa, M; et al. (Gene therapy, 2003)
T-lymphocyte-directed gene therapy has potential as a treatment of subjects with immunological disorders. One current limitation of this therapeutic strategy is low gene transfer efficiency, even when complex procedures are used. We report herein that a recombinant Sendai virus vector (SeV) was able to overcome this issue. Using jellyfish enhanced green fluorescent protein gene (EGFP), we found that SeV was able to transduce and express a foreign gene specifically and efficiently in activated murine and human T cells, but not in naive T cells, without centrifugation or reagents including polybrene and protamine sulfate; the present findings were in clear contrast to those demonstrated with the use of retroviruses. The transduction was selective in antigen-activated T cells, while antigen-irrelevant T cells were not transduced, even under bystander activation from specific T-cell responses by antigens ex vivo . Receptor saturation studies suggested a possible mechanism of activated T-cell-specific gene transfer, ie, SeV might attach to naive T cells but might be unable to enter their cytoplasm. We therefore propose that the SeV vector system may prove to be a potentially important alternative in the area of T-cell-directed gene therapy used in the clinical setting.